Microglia/Macrophages and CD4+CD25+ T Cells Enhance the Ability of Injury-Activated Lymphocytes to Reduce Traumatic Optic Neuropathy In Vitro - Geng, Yiqun; Lu, Zhihao; Guan, Jitian; van Rooijen, Nico; Zhi, Ye (Frontiers in Immunology, 2021)
Inflammation after acute CNS injury plays a dual role. The interplay between immune cells and inflammatory mediators is critical to the outcome of injured neurons. Microglia/macrophages are the first sensors and regulators of the immune response. We previously found that the enhancement of macrophages on neuron survival does not persist in thymectomized rats. How T lymphocytes and macrophages interact and benefit neuron survival is not fully elucidated. To this point, we introduce and characterize a cell-retina co-culture model that mimics the recruitment of peripheral lymphocytes at the injury site. Three-day post-optic nerve transection (ONT) in Fischer 344 rats, transected retinas were co-cultured with either peripheral lymph node-derived lymphocytes (injury-activated) or from intact rats as the control. The injury-activated lymphocytes preserved retinal ganglion cells (RGCs) and caused extensive retina microglial/macrophage infiltration. CD4+CD25+ T cells were upregulated in the injury-activated lymphocytes and increased RGC survival, suggesting that CD4+CD25+ T cells suppressed the cytotoxicity of control lymphocytes. When microglia/macrophages were depleted by clodronate, neuron loss was more extensive, the cytotoxicity of control lymphocytes on RGCs was alleviated, and the neuroprotective effect of injury-activated lymphocytes remain unchanged Cytokine detection showed an increase in IL-6 and TNF-α levels that were reduced with microglia/macrophage depletion. Our results suggest that microglial/macrophage infiltration into axotomized retinas promotes RGC survival by secreting cytokines to induce CD4+CD25+ T cells and suppress T cell-mediated RGC toxicity. These findings reveal a specific role for microglia/macrophage and CD4+CD25+ T cells in inflammation after CNS injury, thereby adding to the mechanistic basis for the development of microglial/macrophage modulation therapy for traumatic CNS injury.